THE CORELATION OF RISK TOWARD PROFIT MARKETING LEVEL OF COCONUT PRODUCTS - Fausayana, Ine; Abdullah, Weka Gusmiarty; Dawid, La Ode (International Journal of Research -GRANTHAALAYAH, 2018)
This study aims to analyze the correlation of risk with the marketing profit of coconut products in Kendari City This research uses qualitative and quantitative methods (deviation standard and probability). The populations of this research are all sellers of grated coconut, young coconut dan young coconut ice in Kendari City. Determination of sample for seller of coconut shredded using simple random sampling, while for seller of young coconut dan young coconut ice by using census. The results of this study are grated coconut products in the normal and surplus sales period have a medium risk level, and critical sales period has a high risk. Young coconut dan young coconut ice in normal and high sales periods have low risk, and in critical sales periods have a medium risk. The correlation of risk and the marketing profit level of coconut products is that high level of risk followed by a low marketing profit, conversely low risk level followed by high marketing profits.